2021
DOI: 10.1186/s12889-020-10041-8
|View full text |Cite
|
Sign up to set email alerts
|

An experience of mass administration of fractional dose inactivated polio vaccine through intradermal needle-free injectors in Karachi, Sindh, Pakistan

Abstract: Background Inactivated Polio Vaccine (IPV) campaign was conducted in February 2019 in Karachi where needle-free injectors were introduced for the administration of the fractional dose of IPV (fIPV) on a large scale. This study aimed to determine the impact of needle-free injectors on vaccination coverage. Methods In four towns of Karachi, fIPV was given using needle-free injectors “PharmaJet Tropis ID”. Whereas, in six towns full dose of IPV was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…We found that people who work in the polio program (i.e., front-line workers) were the main source of awareness regarding the polio campaigns and vaccination, followed by the media (television). A previous study also showed that social mobilization and community health worker visits improved awareness and injectable polio vaccine coverage in the community settings of Karachi, Pakistan [ 16 ]. Our study findings are contrary to those of a study by Facciolà et al, who reported that TV was the main source of the information regarding vaccination in the community [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that people who work in the polio program (i.e., front-line workers) were the main source of awareness regarding the polio campaigns and vaccination, followed by the media (television). A previous study also showed that social mobilization and community health worker visits improved awareness and injectable polio vaccine coverage in the community settings of Karachi, Pakistan [ 16 ]. Our study findings are contrary to those of a study by Facciolà et al, who reported that TV was the main source of the information regarding vaccination in the community [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, patients report a preference and may react less to NFIS delivery compared to traditional delivery methods [ 56 , 57 , 59 , 60 ]. Thus, NFIS are considered an attractive alternative to NS in mass vaccination campaigns [ 57 , 59 , 60 , 65 ], especially in more remote or rural areas with limited resources where delivery via NFIS can also be more cost-effective than NS delivery [ 66 ]. Indications for which NFIS have recently been used to deliver prophylactic DNA vaccines include COVID-19, HIV, Zika, HPV, influenza, dengue, polio, and measles–mumps–rubella viral infections [ 17 , 30 , 54 , 57 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ], staphylococcal and tuberculosis bacterial infections [ 25 , 27 ], and malarial and cryptococcal parasitic infections [ 23 , 28 ].…”
Section: Physical Delivery Methods To Improve Intracellular Dna Vacci...mentioning
confidence: 99%
“…In addition, the use of needles and syringes for administration was associated with the potential for needle re-use. Over past decades, there have been efforts to develop and implement new vaccine-product innovations to overcome some of these delivery and administration barriers and four are described in these case studies ( Box 1 , Box 2 , Box 3 , Box 4 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [17] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [15] , [16] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] ).…”
Section: The Retrospective Innovation Environment: Four Vaccine-product Innovation Case Studiesmentioning
confidence: 99%